Who gives foreign aid to whom and why? - Alesina, Alberto 1957-2020; Dollar, David 1954- (NBER working paper series, 1998)
This paper studies the pattern of allocation of foreign aid from various donors to receiving countries. We find considerable evidence that the direction of foreign aid is dictated by political and strategic considerations, much more than by the economic needs and policy performance of the recipients. Colonial past and political alliances are the major determinants of foreign aid. At the margin, however, countries that democratize receive more aid, ceteris paribus. While foreign aid flows respond more to political variables, foreign direct investments are more sensitive to economic incentives, particularly property rights in the receiving countries. We also uncover significant differences in the behavior of different donors.